EVALUATION OF THE USE OF GOVERNMENT CREDIT CARDS AS A MEANS OF PAYMENT FOR STATE EXPENDITURES TRANSACTIONS AT THE BPK REPRESENTATIVE FOR NORTH SUMATRA PROVINCE - Silvia Febrina Lubis; Meilita Tryana Sembiring; Rulianda Purnomo Wibowo (CV. Radja Publika, 2023)
Management of state finances is part of the government's instruments to achieve the aspired state goal of realizing a just and prosperous society.Management of State Finances is the overall activities of officials managing state finances in accordance with their position and authority, which includes planning, implementation, supervision and accountability. The development process will not run smoothly if state finances are disrupted or unstable. The form of state financial management is reflected in the State Revenue and Expenditure Budget (APBN).